Melioidosis: a potentially life threatening infection - How, Soon Hin; Liam, C K (Malaysian Medical Association, 2006)
Melioidosis is caused by the gram-negative bacillus, Burkholderia pseudomallei. It is endemic in tropical Australia and in Southeast Asian countries. The overall mortality from this infection remains extremely high despite recent advancement in its treatment. This review discuss about clinical manifestations, diagnosis and management of melioidosis.